Extracorporeal Therapy in Dermatology - Sumit Sen; Olympia Rudra; Tirthankar Gayen (Wolters Kluwer Medknow Publications, 2021)
Extracorporeal therapy is a treatment modality where human blood undergoes favorable technical modifications and is reintroduced into the same patient. Since the last four decades this technique has been deployed in the management of difficult and refractory disorders in dermatology. Over a period of time newer techniques like immunoadsorption has emerged and opened new vistas in management of morbid dermatoses. In extracorporeal photopheresis a patient's leukocytes are separated and treated outside with Ultra Violet A in presence of 8-methoxypsoralen. Double filtration plasmapheresis and Immunoadsorption are techniques to remove offending immune complexes. They are safe and reduce the need of toxic medications that are conventionally used in recalcitrant skin diseases. In recent years immunoadsorption is emerging as first-line therapy in condition like immunobullous diseases. High cost is one of the important factors limiting their wider use in developing countries like India. Our review discusses different extracorporeal therapies, their applications, recommendations and guidelines based on various clinical trials.